Do Human Rights laws in Europe adequately deal with Offensive Speech? - Ngcetane-Vika, Thelela (My University, 2023)
It is a widely accepted view that the universal nature of human rights and civil liberties are innate and fundamental in democratic societies. In the aftermath of the Second World War that saw massive human rights violations and bloodbath, the United Nations General Assembly adopted the Universal Declaration of Human Rights in 1948. The adoption of the Universal Declaration of Human Rights(UDRH) still reigns supreme to this day as a backbone of human rights. Those rights include freedom of expression, freedom of association, freedom of religion, right to dignity, right to life, among others. The rise in anti-immigration and anti-Islam rhetoric in political debates across Europe has brought into sharp focus the role of human rights when faced with expression that offends particular groups within society. Thus, the Universal Declaration of Human Rights (UDHR), the European Convention for the Protection of Human Rights, Article 19 of the International Covenant on Civil and Political Rights and Fundamental Freedoms adopted the freedom of expression although worded slightly different on each but the principles are similar. The empirical basis for this paper has included mostly primary and secondary sources, including literature review on books, articles, reading annual UN and EU reports, global reports and relevant Statutes. This project is structured to include; firstly, an analysis of key frameworks that include the human rights, especially freedom of speech and offensive speech. Secondly, concluding a summary of the essence of the research and key findings. Those include that freedom of speech rights come with responsibilities. Thus, Legislative interventions and court precedents continue to bring legal and judicial clarity on what is an offensive speech.
Keywords: Civil Liberties; Europe; Human Rights Laws; Offensive Speech; Universal Declaration of Human Rights